2005
DOI: 10.1002/marc.200400534
|View full text |Cite
|
Sign up to set email alerts
|

Re‐Gradation of Photo‐Oxidized Post‐Consumer Greenhouse Films

Abstract: Summary: The degradation undergone by the polymers during their use and because of the thermo‐mechanical degradation undergone during the reprocessing operations provokes, among other effects, the decrease of the molecular weight. The change of the molecular architecture is responsible for the deterioration of all the properties. In order to restore the properties of post‐consumer recycled plastics, some rebuilding of the molecular structure is necessary. In this work, photo‐oxidized films for greenhouses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The addition of new stabilisers during recycling (restabilisation) may help to both protect the thermo‐mechanical degradation during processing and enhance the long‐term stability of the recycled products, but is not enough to improve their mechanical properties and performance. Modification of the chemical structure and molecular architecture of the recyclates is needed to upgrade effectively the properties of recycled products; this approach has been inspiringly designated as “rebuilding” by La Mantia and co‐workers 89–92. The use of certain additives during mechanical recycling, such as radical generators or compounds with reactive functional groups, can be effective in inducing branching or crosslinking reactions in the degraded polymeric chains from waste materials during melt reprocessing (reactive extrusion); this increases the molecular weight of the chains and improves rheological and mechanical properties.…”
Section: Upgrading Recycled Plasticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of new stabilisers during recycling (restabilisation) may help to both protect the thermo‐mechanical degradation during processing and enhance the long‐term stability of the recycled products, but is not enough to improve their mechanical properties and performance. Modification of the chemical structure and molecular architecture of the recyclates is needed to upgrade effectively the properties of recycled products; this approach has been inspiringly designated as “rebuilding” by La Mantia and co‐workers 89–92. The use of certain additives during mechanical recycling, such as radical generators or compounds with reactive functional groups, can be effective in inducing branching or crosslinking reactions in the degraded polymeric chains from waste materials during melt reprocessing (reactive extrusion); this increases the molecular weight of the chains and improves rheological and mechanical properties.…”
Section: Upgrading Recycled Plasticsmentioning
confidence: 99%
“…The use of certain additives during mechanical recycling, such as radical generators or compounds with reactive functional groups, can be effective in inducing branching or crosslinking reactions in the degraded polymeric chains from waste materials during melt reprocessing (reactive extrusion); this increases the molecular weight of the chains and improves rheological and mechanical properties. This procedure has been successfully applied to upgrade degraded post‐consumer PE from greenhouse films89, 90, 92 and pipes 91…”
Section: Upgrading Recycled Plasticsmentioning
confidence: 99%
“…Different strategies have been adopted to decrease the negative effect of the degradation on the final properties of postconsumer plastics, like stabilization,11–18 regradation,19–21 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the synergistic effect of oxygen, temperature, and UV radiation during the lifetime cause relevant damages in the chemical structure and morphology and, consequentely, in the mechanical and optical properties of the postconsumer material, while the combined effect of temperature and stress gives rise more degradation. [4][5][6][7][8][9][10] Different strategies have been adopted to decrease the negative effect of the degradation on the final properties of postconsumer plastics, like stabilization, [11][12][13][14][15][16][17][18] regradation, [19][20][21] etc.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work8 it has been demonstrated that the use of suitable additives can enlarge the molecular weight distribution or can create branching and cross‐linking during the melt processing of the photo‐oxidized PE. An increase of the molecular weight enhances the rheological and the mechanical properties of the recycled material.…”
Section: Introductionmentioning
confidence: 99%